Submesoscale streamers exchange water on the north wall of the Gulf Stream. Issue 3 (10th February 2016) - Klymak, Jody M.; Shearman, R. Kipp; Gula, Jonathan; Lee, Craig M.; D'Asaro, Eric A.; Thomas, Leif N.; Harcourt, Ramsey R.; Shcherbina, Andrey Y.; Sundermeyer, Miles A.; Molemaker, Jeroen; McWilliams, James C.
Abstract: The Gulf Stream is a major conduit of warm surface water from the tropics to the subpolar North Atlantic. Here we observe and simulate a submesoscale (<20 km) mechanism by which the Gulf Stream exchanges water with subpolar water to the north. Along isopycnals, the front has a sharp compensated temperature‐salinity contrast, with distinct mixed water between the two water masses 2 and 4 km wide. This mixed water does not increase downstream despite substantial energy available for mixing. A series of streamers detrain this water at the crest of meanders. Subpolar water replaces the mixed water and resharpens the front. The water mass exchange accounts for a northward flux of salt of 0.5–2.5 psu m 2 s −1, (large‐scale diffusivity O (100 m 2 s −1 )). This is similar to bulk‐scale flux estimates of 1.2 psu m 2 s −1 and supplies fresher water to the Gulf Stream required for the production of 18° subtropical mode water. Key Points: Lateral detrainment clearly observed from North Wall at depth Salt flux similar to bulk estimates Detrained water is from a distinct partially mixed water class